HUBUNGAN KOORDINASI MATA TANGAN DENGAN KEMAMPUAN PASSING ATAS PADA PERMAINAN BOLA VOLI MAHASISWA JURUSAN ILMU KEOLAHRAGAAN ANGKATAN 2018 FKIP UHO - Asmida Asmida; Wolter Mongsidi; Badaruddin Badaruddin (JOKER (Jurnal Ilmu Keolahragaan), 2020)
The purpose of this study was to determine the correlation between eye and hand Coordination with overhead passing ability of volleyball games at the students  of sports sciences in academic year 2018, teacher training and education faculty at halu oleo university. The population in this study were all students of sports sciences in academic year 2018, teacher training and education faculty at halu oleo university, amounted to 73 people consist of 54 boys and 19 girls. The sample in this study was taken based on a purposive sampling technique that is based on consideration of male obtained by 54 people, the based on students who are able to done overhead passing getting 32 people who were sampled in this study.The instrument is used to measure eye and hand Coordinationmic by throwing the ball to the wall repeatedly for 30 seconds, while to measure overhead passing ability with a test of overhead passing repeatedly by overhead.                Based on the product moment correlation test on the observed variables, it can be expla that  there is a significant correlation between eye and hand Coordination with overhead passing ability rxy= 0.40>rtable (0.05:32), its means that there is a significant correlation between eye and hand coordination with overhead passing ability of volleyball games at students of sports sciences in academic year 2018, teacher training and education faculty at halu oleo university, with coefficient determination (r2)= 0.16.             Based on the results of this analysis, it can be concluded that there is a significant correlation between eye and hand coordination with overhead passing ability of volleyball games at halu oleo university. Eye and hand coordination contributed to 16% at the overhead passing ability of volleyball games, while 84% was influenced, by other physical conditions such as strength, accuracy, speed, agility, balance, flexibility, endurance, and reaction.